General geology and characterization of clay properties in Jeli, Kelantan - Nurul Jannah Abdul Latif (2017)
A study on the general geology and the characterization of clay properties was conducted in Jeli, Kelantan. The geological map of the study area has been produced and updated by using Geographic Information System (GIS) method. Based on the geological map, this study area mainly composed of granitic rocks. The presence of gneiss in the study area indicates that minerals of previous igneous rock have undergone alignment or foliation that lead to the classification of metamorphic rocks. Gneiss is resulted when the granite rock subjected to high pressure and temperature. Five clay samples have been collected from the study area where the areas are surrounded by granitic rocks. The mineral associations found in the clay samples were identified as feldspar, mica and quartz. X-Ray Diffraction (XRD) and X-Ray Fluorescence (XRF) analysis were conducted in order to identify the clay properties in this study area. The elements detected in the clay samples mainly Si, Al, Fe, Ti and K. The percentage of elemental content depending on location which ranged between 48.6% - 59.8% for Si, 19.4% - 29.3% of Al, 3.73% - 18.6% of Fe, 0.302% - 2.34% of Ti and 0.523% - 12.1% of K. The clay samples presence in this study area probably kaolinite and illite as observed from the chemical analysis as well as study the literature review.